A model of adaptation for families of elderly patients with dementia: focusing on family resilience. (3rd October 2018) - Kim, Geun Myun; Lim, Ji Young; Kim, Eun Joo; Kim, Sang Suk
ABSTRACT: Objectives: We constructed a model explaining families' positive adaptation in chronic crisis situations such as the problematic behavior of elderly patients with dementia and attendant caregiving stress, based on the family resilience model. Our aim was to devise an adaptation model for families of elderly patients with dementia. Method : A survey of problematic behavior in elderly patients with dementia, family stress, family resilience, and family adaptation was conducted with 292 consenting individuals. The collected data were analyzed using structural equation modeling. Results: The communication process, family stress, and problematic behavior of elderly patients with dementia had direct and indirect effects on family adaptation, while belief system, organization pattern, and social support had indirect effects. Specifically, family stress and more severe problematic behavior by elderly patients with dementia negatively influenced family adaptation, while greater family resilience improved such adaptation. Conclusion: Interventions aiming to enhance family resilience, based on the results of this study, are required to help families with positive adaptation. Such family programs might involve practical support such as education on the characteristics of elderly persons with dementia and coping methods for their problematic behavior; forming self-help groups for families; revitalizing communication within families; and activating communication channels with experts.